Isolated Mitral Valve Repair in Patients with Reduced Left Ventricular Ejection Fraction - Noack, Thilo (Ann Thorac Cardiovasc Surg, 2019)
Purpose: This study aims to analyze the clinical outcomes after isolated mitral valve (MV) repair in patients with reduced left ventricular ejection fraction (LVEF <50%) with focus on perioperative characteristics, survival, and freedom from reoperations. Methods: Between 1997 and 2015, 557 patients with reduced LVEF (age: 62.8 ± 11.7 years, male: 320) underwent MV repair for symptomatic mitral regurgitation (MR). Etiologies were dilated non-ischemic cardiomyopathy and ischemic cardiomyopathy in 487 (87.4%) and 70 (12.6%) patients, respectively; these were classified into three different subgroups: LVEF 40%–49% (group 1), 30%–39% (group 2), and <30% (group 3). Results: Overall, 294, 145, and 118 patients had an LVEF of 40%–49%, 30%–39%, and <30%, respectively. Logistic EuroSCORE was significantly higher (P <0.001) as the LVEF worsened. The survival analysis for groups 1–3, respectively, revealed the following: 30-day mortality: 1.4%, 3.4%, and 7.6% (P <0.001); 1-year survival: 93.9%, 89.4%, and 82% (P <0.001); 5-year survival: 81.2%, 75.2%, and 58% (P <0.001). Conclusion: MV repair in patients with impaired LVEF could be performed safely with good clinical short- and mid-term outcome. Nevertheless, reduced preoperative LVEF correlates with worse perioperative and long-term survival.